2020
DOI: 10.1109/access.2020.3040043
|View full text |Cite
|
Sign up to set email alerts
|

Work-Based Learning Conceptual Framework for Effective Incorporation of Soft Skills Among Students of Vocational and Technical Institutions

Abstract: The importance of soft skills has been recognized in most fields, hence, various companies make judgments on work and success evaluation based largely on employees' soft skills. Work-Based Learning (WBL), as an educational approach, can harness students' potential in soft skills. This investigation aimed to generate a conceptual framework for WBL to effectively integrate soft skills among students in technical colleges. A sample of 268 technical teachers was drawn from a population of 302 technical teachers fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…The exponential growth of technology and internet connectivity has given rise to a modern world that has had an impact on all aspects of people's lives. The complexities of labor advertising for scholastically discharged youthful graduates, the requirement for social relations between regions, and insufficient social imply, to name a few factors, have increased the risk of youth disengagement from occupations [12]. In spite of exceptionally considerable speculation, the introduction of computers and other ICT apparatuses into the classroom is a larger part of specialized and professional instruction.…”
Section: Research Motivationmentioning
confidence: 99%
“…The exponential growth of technology and internet connectivity has given rise to a modern world that has had an impact on all aspects of people's lives. The complexities of labor advertising for scholastically discharged youthful graduates, the requirement for social relations between regions, and insufficient social imply, to name a few factors, have increased the risk of youth disengagement from occupations [12]. In spite of exceptionally considerable speculation, the introduction of computers and other ICT apparatuses into the classroom is a larger part of specialized and professional instruction.…”
Section: Research Motivationmentioning
confidence: 99%
“…Moreover, the project aimed at developing soft (non-technical) skills, including interpersonal and behavioural skills in the workplace (Ngang, Yie, and Shahid, 2015), which involve little or no interaction with machines. However, soft skills are essential for personal development (Taylor, 2016), effective collaboration and communication (Weichbroth, 2022;Weston, 2020), ultimately contributing to building relations among employees and their work effectiveness (Dogara, Saud, and Kamin, 2020;Wieczorkowski, Chomiak-Orsa, and Pawełoszek, 2022). In this context, the two objectives concerned:…”
Section: Project Goals and Scopementioning
confidence: 99%
“…apply their acquired knowledge to real problems [10]. Moreover, some practices have shown that engineering students are motivated to learn complex concepts when they can solve real-life problems through projects and teamwork [11], [12], such as active learning [13], [14].…”
Section: Introductionmentioning
confidence: 99%